2006
DOI: 10.1021/bi0519506
|View full text |Cite
|
Sign up to set email alerts
|

Double Mutation at the Subunit Interface of Glutathione Transferase rGSTM1-1 Results in a Stable, Folded Monomer

Abstract: Canonical glutathione (GSH) transferases are dimeric proteins with subunits composed of an N-terminal GSH binding region (domain 1) and a C-terminal helical region (domain 2). The stabilities of several GSH transferase dimers are dependent upon two groups of interactions between domains 1 and 2 of opposing subunits: a hydrophobic ball-and-socket motif and a buried charge cluster motif. In rGSTM1-1, these motifs involve residues F56 and R81, respectively. The structural basis for the effects of mutating F56 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 24 publications
3
28
0
Order By: Relevance
“…1D). The substitution of charged residues, such as Asp, Arg, and Glu into a protein dimer or oligomer interface has been shown to be a viable approach for preparing monomeric enzymes (25,(37)(38)(39).…”
Section: Resultsmentioning
confidence: 99%
“…1D). The substitution of charged residues, such as Asp, Arg, and Glu into a protein dimer or oligomer interface has been shown to be a viable approach for preparing monomeric enzymes (25,(37)(38)(39).…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been suggested that the hydrophobic lock and key interaction is the major interaction between subunit interfaces in all GSTs (7,14,15,25,34,35), the electrostatic attractions definitely enhance the interaction between subunits and play an important role at the dimer interface (22,23,25,36). Electrostatic interactions have also been shown to be involved in both the catalytic reaction and the subunit interactions of the ␦ class GST of Anopheles dirus (37,38) and of the cephalopod class GST (39).…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, amino acid substitutions at the contact interface lead to the dissociation of oligomeric enzymes into subunits with more or less reduced reaction rates and conformational stabilities. [7][8][9][10][11] The members of the phosphoribosyltransferase (PRT) enzyme class catalyze the transfer of a phosphoribosyl group to an aromatic base. PRTs have an important role in the metabolism of nucleotides and amino acids; for example, as key components of the purine salvage and the histidine and tryptophan biosynthetic pathways.…”
Section: Introductionmentioning
confidence: 99%